BAHASA CANGKRUKAN DI ANGKRINGAN (KAJIAN SOSIOLINGUISTIK) - Sindhu Linguistika Manumasa (Translation and Linguistics (Transling), 2024)
This research is based on the phenomenon of the emergence of language variations that occur and the influencing factors in the cangkrukan language in angkringan. Communication that occurs in angkringan between visitors and sellers gives rise to language variations. It describes the forms of language variation that arise and the factors that influence them. To uncover these problems by using a Sociolinguistic approach, while still looking at the phenomena that occur in angkringan. This study used the qualitatitf method. The research data is a speech taken from two angkringan in Semarang City, namely angkringan Givan and angkringan Pak Wandi. Data is collected through direct observation, using the listening method which includes the technique of listening freely involved and tapping techniques accompanied by recording and recording techniques. The results showed the emergence of forms of language variation in the form of code mix, interference, abreviation and analogy. Factors that influence the emergence of language variations are environmental factors, age factors and practicality factors in communication.